Public Ethics and HR Governance in Public Administration - Rojak, Jeje Abdul (Bulletin of Science, Technology and Society, 2024)
This research examines the role of public ethics and Human Resources (HR) governance in public administration as key elements in creating effective and accountable governance. Using a normative juridical approach based on a literature study, this research identifies the challenges of implementing public administration ethics in Indonesia, including corruption, abuse of authority, and bureaucratic pathology. It explores strategies for strengthening public ethics through HR governance policies that are integrated with the values of justice and transparency. The study found that the implementation of public ethics still faces structural, cultural, and lack of regulatory enforcement constraints. HR governance based on meritocracy has proven to be a potential solution to improve bureaucratic integrity. This research highlights the importance of synergy between the principles of public ethics and HR governance to promote good governance in Indonesia. The results of this research contribute to the legal and public administration literature and serve as a reference in the preparation of relevant policies.